Pengaruh Latihan Feeding Terhadap Hasil Pukulan Forehand Drive dan Backhand Drive Tenis Lapangan - Wimba Tegar Prastawa; Husnul Hadi; Galih Dwi Pradipta (YLPK Mahardhika, 2022)
This research is a Quasi Experiment using a quantitative approach. The population in the study was all players of the annual Kepodang Tennis club, amounting to 6 people. The sampling technique was simple random sampling. The data analysis technique in this study used the t-test statistic. The instrument uses a feeding exercise program using a forehand drive and backhand drive that has been approved and approved by an expert lecturer for use as a research instrument. The results of the analysis of the feeding practice have an effect on the technique of hitting the forehand drive in the tennis court of the members of the Annual Kepodang Club, Jepara Regency. This is based on the practice results of tennis players in straight forehand drives increased by 21% and cross-directional forehand drives increased by 21%. Feeding practice affects the backhand drive technique of tennis court members of the Annual Kepodang Club of Jepara Regency. This is based on the practice results of tennis players in straight backhand drive increased by 21% and cross backhand drive increased by 15%. It can be concluded that the use of the feeding training model is effective against the forehand drive and backhand drive of the tennis court at the Kepodang Annual Jepara Tennis Club, and there is no significant difference between the of the feeding training model on forehand drive strokes and the feeding training model for backhand drive strokes